2011 4th IFIP International Conference on New Technologies, Mobility and Security 2011
DOI: 10.1109/ntms.2011.5720580
|View full text |Cite
|
Sign up to set email alerts
|

Message Denial and Alteration on IEEE 802.15.4 Low-Power Radio Networks

Abstract: Abstract-Protection against the attacks through both academic and industry-developed standards is briefly discussed.Keywords-constrained devices, denial of service, low-power networks, security, man in the middle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…These are mainly based on jamming techniques which can lead to more serious DoS and man in the middle attack. The work in [40] showed that the additional security towards sweep and reactive jamming could be provided by the IEEE 802.15.4.e amendment with channel hopping. Also, authors proposed data encryption to prevent data denial.…”
Section: Attacks and Security Mechanisms For Phy And Mac Layer Commmentioning
confidence: 99%
See 1 more Smart Citation
“…These are mainly based on jamming techniques which can lead to more serious DoS and man in the middle attack. The work in [40] showed that the additional security towards sweep and reactive jamming could be provided by the IEEE 802.15.4.e amendment with channel hopping. Also, authors proposed data encryption to prevent data denial.…”
Section: Attacks and Security Mechanisms For Phy And Mac Layer Commmentioning
confidence: 99%
“…However, as the encryption covers only MAC payload, an adversary might be able to read the 802.15.4 MAC header and decide on taking an action which can seriously affect the network. For example, if an adversary changes the frame counter or injects false data, that frame will be finally rejected, but it will waste some energy [40]. An additional threat to IEEE 802.25.4 comes from the fact that there is no integrity protection provided on ACK frames, so the eavesdropper can forge the ACK frame and fool the sender of the successful reception of the frame.…”
Section: Attacks and Security Mechanisms For Phy And Mac Layer Commmentioning
confidence: 99%
“…An attacker can deliberately use radio jamming to cause denial of service. In [19], three types of radio jamming attacks against 802.15.4 are implemented in hardware including:…”
Section: Radio Jammingmentioning
confidence: 99%
“…At that time, the ZigBee family of protocols were solely layered on the IEEE 802.15.4 MAC layer standard. Some research, targeted solely at the 802.15.4 MAC layer, identified security concerns (see Sokullu, 2008;O'Flynn, 2011). Exploitation of these security issues could bring the link to the network down but would not provide access to application layer packet contents.…”
Section: Han Architecturementioning
confidence: 99%